Realty beyond the traditional blueprints of art & gentrification : a reader - Zolghadr, Tirdad 1973- (Hatje Cantz, 2022)
How to transcend land grab economies, even by means of art? The reader REALTY moves from the safety of critique to the vulgarity of suggestions. The pandemic?s effect on mobility presents a historic opportunity. Rarely has criticism of our extractive artworld logic of one-place-after-another been louder. REALTY is a long-term curatorial program by Tirdad Zolghadr (*1973), initially commissioned by the KW Institute for Contemporary Art. With the help of numerous artists and experts who contributed over 2017?2020, this reader revisits how contemporary art can contribute to decisive conversations on urbanism.00TIRDAD ZOLGHADR (*1973) is a curator and writer. He is currently artistic director of the Sommerakademie Paul Klee. Curatorial work over the last two decades includes biennial settings as well as long-term, research-driven efforts, most recently as associate curator at KW Institute for Contemporary Art Berlin, 2016-20
Keywords: Geschichte 2017-2020; Engagierte Kunst; Rezeption; Gentrifizierung; Landnahme; Art and society; Art and cities; Urban renewal; Art, Modern / 21st century; Urban Renewal; Rénovation urbaine; Art / 21e siècle; Art et société; urban renewal; Art, Modern; 2000-2099